2011
DOI: 10.1186/1756-9966-30-70
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of SMAD4 in gliomas correlates with progression and survival of patients

Abstract: BackgroundTo examine the expression of SMAD4 at gene and protein levels in glioma samples with different WHO grades and its association with survival.MethodsTwo hundreds fifty-two glioma specimens and 42 normal control tissues were collected. Immunochemistry assay, quantitative real-time PCR and Western blot analysis were carried out to investigate the expression of SMAD4. Kaplan-Meier method and Cox's proportional hazards model were used in survival analysis.ResultsImmunohistochemistry showed that SMAD4 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 16 publications
3
16
0
1
Order By: Relevance
“…Further, a recent study demonstrated that decreased levels of both SMAD4 mRNA and protein in glioma compared to normal (P < 0.001). There was a gradual decrease in SMAD4 expression levels from grade I to grade IV glioma [22]. The survival rate of SMAD4-positive patients was higher than that of SMAD4-negative patients and demonstrated that the loss of SMAD4 was a significant and independent prognostic indicator in glioma.…”
Section: Discussionmentioning
confidence: 91%
“…Further, a recent study demonstrated that decreased levels of both SMAD4 mRNA and protein in glioma compared to normal (P < 0.001). There was a gradual decrease in SMAD4 expression levels from grade I to grade IV glioma [22]. The survival rate of SMAD4-positive patients was higher than that of SMAD4-negative patients and demonstrated that the loss of SMAD4 was a significant and independent prognostic indicator in glioma.…”
Section: Discussionmentioning
confidence: 91%
“…Here, we demonstrated that M146-exo decreased EGFR and NF-κB protein in 9L glioma cells in vitro . miR-146b has also been identified to inhibit SMAD4, the loss of which is a independent indicator of poor outcome in glioma [7, 10]. Therefore, it is likely that concurrent inhibition of factors in addition to EGFR underpins the anti-tumor effect of M146-exo.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that SMAD4 was considered as a tumor suppressor and was frequently mutated or homozygously deleted in pancreatic cancer and colorectal cancer [11], [12], [13]. Loss expression of SMAD4 was associated with poor clinical outcomes in patients with pancreatic, colon, and brain cancers[14], [15], [16]. Although mutation and homozygous deletion of SMAD4 were rare in head and neck squamous cell carcinoma (HNSCC)[17], knockout SMAD4 could lead to spontaneous oral squamous cell carcinoma development in an animal model[18], suggesting the tumor suppressor role of SMAD4 in oral tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%